Test the Adaptability of Several Soybean (Glycine Max L) F5 Strains with TSP Fertilizer - Arvita Netti Sihaloho; Irawaty Rosaline; Wahyunita Sitinjak (Postgraduate, University of Mataram, 2023)
Growth and production strains need to be capability tested in many different environmental conditions. The research aims to obtain efficient strains against the use of phosphate fertilizer and obtain the best dose of TSP fertilizer for the growth and production of soybean strains. The study used the two-factor Factorial Group Randomized Design (RAKF) method. The first factor is the dose of TSP fertilizer with 3 levels, namely P1=25 kg/ha, P2=50 kg/ha, P3=75 kg/ha.The second Factor with 5 levels, treatments were obtained and repeated 3 times. The plot area is 1mx2m with a planting distance of 20 cm x 25 cm. Plant maintenance is carried out by spraying insecticides Decis 25 EC and Dithane. The variables observed were plant height (cm), number of productive branches (branches), number of pods per plant (pods), seed weight per plant (g), seed weight per plot (g), weight of 100 seeds (g). DataÂ were analyzed with a 95% confidence level BNT test using SPSS 26. The results showed that the F5 strain is the most efficient strain in using TSP fertilizer is the G4 = F5-A-T-SSD-84 strain with a dose of 25 kg/ha or 75g/plot to produce planting seed weight 27.76g. TSP fertilizer dose of 75 kg/ha is the best dose to produce the highest planting seed weight